(untitled) (Journal of University of Babylon for Engineering Sciences, 2020)
Asphalt mixtures have great potentials as electrical connectors for many functions in the field of self-sensing, hospitalization and energy collection. Electrical conductivity (EC) controls the pouring of asphalt concrete to a priority stage for such presentations, taking into account some additives that minimize damage to basic materials over time. Previously fibre conductivity tests are used in the conductivity of the asphalt mixture. There is now a need for mitigation due to the sudden change in the ER electrical curve of the filtration conditions of the down mixtures, considering the sudden transition from the electrical resistivity (ER) values ​​to the conduction phase (EC). Efficient clay mixtures to relieve defects of sudden changes are considered eco-friendly. Therefore, this study looks for an output where encapsulation efficiency used by directing the electrical conductivity (EC) of asphalt concrete only by adding a specific content of bentonite content in the kaolin-dominant mixture between (KB0.1) to (KB0.4). Therefore, eight different types of clay mixture KB0.1 to KB0.4 and Kaolinite 0.9-Sand 0.1 to KS0.4 have different geophysical properties and different geotechnical parameters. EC values. ER values are evaluated by asphalt-mixed samples containing different contents of the dominant K-clay mixture.